2011
DOI: 10.1111/j.1532-5415.2010.03289.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nosocomial Bloodstream Infections in Older Adults

Abstract: MRSA is a common cause of CRBSI in older adults. Male sex, obesity, the presence of a central line, a gastrostomy tube, and urinary incontinence at the time of admission were independent predictors of BSI in hospitalized older adults. The prediction model constructed in this study should be validated prospectively in a different cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
1
28
0
4
Order By: Relevance
“…With regard to specific infection sites, the present study demonstrates that obesity class I–III patients with cirrhosis have higher prevalence of bacteraemia, UTI and skin and soft tissue infection than non‐obese patients with cirrhosis. Our data regarding bacteraemia and UTI prevalence are consistent with evidence from prior studies of obese individuals in the general population, although ours is the first to corroborate this in the cirrhotic population . Our analysis additionally shows that obese patients have a lower prevalence of SBP compared to non‐obese individuals.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to specific infection sites, the present study demonstrates that obesity class I–III patients with cirrhosis have higher prevalence of bacteraemia, UTI and skin and soft tissue infection than non‐obese patients with cirrhosis. Our data regarding bacteraemia and UTI prevalence are consistent with evidence from prior studies of obese individuals in the general population, although ours is the first to corroborate this in the cirrhotic population . Our analysis additionally shows that obese patients have a lower prevalence of SBP compared to non‐obese individuals.…”
Section: Discussionsupporting
confidence: 91%
“…A retrospective study showed that obesity is an independent predictor of blood stream infection. 7 Other previous studies have shown a correlation between obesity and septic shock, ventilator-associated pneumonia, 8 catheter-associated sepsis, 9 H1N1 influenza infection, 10 and Clostridium difficile infection. 11 Moreover, obesity may alter the course of infection and seems to contribute to the progression of some chronic viral infections such as hepatitis C. [12][13][14] Urinary tract infection (UTI) is one of the most commonly acquired bacterial infections in ambulatory and hospitalized populations.…”
Section: Introductionmentioning
confidence: 90%
“…53 Cohort studies indicate an association between obesity and the risk of nosocomial infections. 12,54 A recent retrospective case-control study has shown obesity to be an independent predictor of nosocomial bloodstream infection in older adults. 54…”
Section: Nosocomial Infections and Surgical Infectionsmentioning
confidence: 99%
“…12,54 A recent retrospective case-control study has shown obesity to be an independent predictor of nosocomial bloodstream infection in older adults. 54…”
Section: Nosocomial Infections and Surgical Infectionsmentioning
confidence: 99%